Evaluating and improving the anti-crisis plans in Russia and worldwide under COVID-19 pandemics. Specific features of crisis management in the state - D. V. Manushin (Russian Journal of Economics and Law, 2020)
Objective: based on a critical assessment of the anti-crisis plans of the Russian Federation and other states, the positions of scientists and experts, to propose measures to correct these plans to improve the quality of management of the Russian economy. To generalize the possibilities of applying the experience of neutralizing the crisis consequences in the framework of the views of existing economic schools.Methods: the research uses such techniques of abstract-logical method as analysis, synthesis, generalization, comparison, analogy, deduction, induction, and prediction.Results: the author analyzes the anti-crisis plan of Russia and reveals the shortcomings of the Russian national plan, which ensures the restoration of employment and income of the population, economic growth and long-term structural changes. The article summarizes foreign practices, some of which are recommended to be implemented in the Russian economy. Recommendations for correction of the studied anti-crisis plans are offered. Taking into account the identified shortcomings and some foreign practices, the anti-crisis plan of the Russian Federation is proposed to be adjusted in the fields of: support for import substitution; improvement of social support of the population; development of exports; modernization of national economy sectors, improvement of taxation; promotion of digitalization; improvement of the quality of work of the Russian regions. The actions to be included in the M. V. Mishustin’s anti-crisis plan are defined.It is revealed that the actions of the Russian Federation Government under the pandemic clearly show the priority of solving non-economic problems over economic ones. This may indicate that crisis management is implemented within the framework of the traditional institutionalism paradigm.Scientific novelty: first, a new direction of economic theory development is proposed - anti-crisis traditional institutionalism, or management of economic crises from the viewpoint of traditional institutionalism. Second, the relevance of the little-known theory of infinite crises and infinite crisis management is confirmed. Third, new measures are proposed for managing the Russian state in times of obvious and hidden crises. Many of them are of an organizational nature, which fully corresponds with the priorities outlined above.Practical significance: the proposed measures can be used to improve crisis management in the Russian economy. The development of economic theory according to the proposed scheme will lead to a change in the structure of objects and methods of anti-crisis management, which will clarify the methodology of anti-crisis management of macro-economy.